MANAJEMEN KEUANGAN PENDIDIKAN MASA PANDEMI COVID 19 DI SEKOLAH SMP ISLAM TERPADU RIYADLUL QUR’AN - febrianti, elfi; eli, eli; nyta, lula (Journal of Management Review, 2024)
Finance in educational institutions is one of the determining factors for the quality of learning. So that financial management becomes very important in an educational institution in order to achieve educational goals. Especially during the COVID-19 pandemic, it is a challenge for educational institutions to manage financial management. The purpose of this study was to determine the implementation of educational financial management during the COVID-19 pandemic at the Riyadlul Qur'an Integrated Islamic Junior High School. This study uses a qualitative approach. The research was conducted at the Riyadlul Qur'an Integrated Islamic Middle School. Data collection techniques were carried out by interview, observation, and documentation study. Data processing techniques were carried out by data reduction. Financial management is carried out starting from financial planning, implementation of financial management, and supervision. Financial planning at the Riyadlul Qur'an Integrated Islamic Junior High School is based on a needs analysis and adjusted to the source of school income. The implementation of financial management during the COVID-19 pandemic is appropriate, there is no difference between income and budget with the percentage of budget fulfillment reaching 100%. However, there are two standards that are not included in the RKAS because during the COVID-19 pandemic, the financing for these standards was transferred to another standard. Meanwhile, the process of financial supervision is carried out by the school's internal and external parties